Effect of Short Period Simultaneous Stimulation of Transcranial Direct Current Stimulation (tDCS) on Occupational Therapy to Motor Function of Upper Extremity in Stroke Subject - Adrian Utomo; I Lukitra Wardhani; I Putu Alit Pawana (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
ABSTRACTObjective: Stroke could cause upper extremity motor function disturbances that may affect to quality of life. The affected brain has an ability to get recovery by neuroplasticity process. Transcranial direct current stimulation (tDCS) is a non-invasive modality that could induce brain neuroplasticity Goal: To determine the effect of tDCS stimulation on recovery of upper extremity motor function in subacute ischaemic stroke patient. Methods: 22 stroke patients included in inclusion criteria, divided into 2 groups, control group and intervention group. Control group had occupational therapy for 5 days consecutively and intervention group had occupational therapy and tDCS stimulation simultaneously for 5 days consecutively. Upper extremity motor function was evaluated with Fugl-Meyer Assessment (FMA) before and after the treatment. Results: Significant improvement of FMA score on control group (p=0,018) and intervention group (p=0,000). Comparison of the result after the treatment revealed that the intervention group showed more significant improvement in FMA score than the control group (p=0,000). Conclusion: Application of tDCS stimulation on occupational therapy simultaneously showed improvement of upper extremity motor function in subacute ischaemic stroke patient better than only occupational therapy. Key Words: Transcranial direct current stimulation, occupational therapy, Fugl-Meyer Assessment, upper extremity motor function, subacute ischemic stroke.